Role of Ghrelin in gastric cancer (Jichu yixue yu linchuang)
Ghrelin is a newly discovered gastrointestinal peptide that is involved in regulating the body's growth, development and energy balance, and plays a key role in the occurrence and progression of malignant tumors, such as cell proliferation, migration, invasion, apoptosis, inflammatory response and vascular disease. Generate immune cell infiltration and so on. Ghrelin affects the progression of gastric cancer by activating NF-κB/p65 and AMPK and other signaling pathways. Ghrelin not only assist in early screening of gastric cancer, but also function a new marker for predicting the prognosis and survival of gastric cancer patients. Ghrelin and its analogs have clinical application value in the treatment of gastric cancer-related syndromes such as cachexia or sarcopenia.